Public-Private Partnerships: In the Development of the Mandalika Circuit, Indonesia - Ilham Zitri; Cahyadi Kurniawan; Theresia Octastefani (Journal of Governance and Public Policy, 2024)
When the government is constrained regarding human and financial resources, a public-private partnership (PPP) is often considered the most effective method of providing infrastructure. As a result, the government can work with the private sector to promote the successful implementation of infrastructure projects. This study examined how the public and private sectors worked together to build the Mandalika Circuit. In addition, this investigation utilized a descriptive method combined with a qualitative approach, as well as literature, online news, and interviews as data. NVivo 12 Plus was employed to analyze the data. The results unveiled the implementation of development programs through regulations, such as Presidential Regulation (Perpres) No. 38 of 2015, Minister of Finance Regulation (Permenkeu) No. 260/PMK.08/2016, Minister of Home Affairs Regulation (Permendagri) No. 96 of 2016, and Governor Decree of West Nusa Tenggara No. 050.13-326 of 2022. Second, the readiness of the PPPs to construct the Mandalika Circuit was considered successful in terms of institutional coordination, which ran well between the regional government, central government, and the private sector. Players could boost productivity and adaptability. Moreover, the presence of non-governmental parties was based on a need for more human and financial resources to manage public services in the government sector strategically.